PENAMAAN KEDAI KOPI DI MAGELANG: KAJIAN ETNOLINGUISTIK - Astuty Astuty (Jurnal Inovasi Penelitian, 2021)
Naming process can be stated as a hope, that is why it is important to think more in giving name for something or labeling things. It can be shown in the naming process of the business, one of the business which needs naming process is coffee shop. Coffee shop becomes a new trend in Surabaya lately. The changing era makes naming process for coffee shops more diverse. The coffee shops’ naming not only uses Indonesian, but they use local language and foreign language, and this phenomenon is really interesting to be studied. The purpose of this research is to observe the meaning of the coffee shops from the semantic side. The researcher used ten coffee shops in Surabaya which have "feeling" theme. After did the research by adding the interview with the owners, it can be concluded that the naming process of the coffee shops contain the owner's hopes and explaining the concept of the coffee shop itself